Gaining competitive advantage through the balanced scorecard - Gomes, Jorge (2022)
One of the most important questions emerged of an intense debate in the field of strategic management is: “how do firms achieve competitive advantage?”. Competitive advantage is seen as the main source to explain the superior firm’s performance, and thus comes to represent the fundamental aim of strategic management. The Porter’s view (1985) popularized by the Harvard Business School raised from the Industrial Organization paradigm (Bain, 1959; Mason, 1949) and emphasized that competitive advantage is the most important and influential mechanism for explaining the superior organizational performance. From the 70s, various currents of economic thought address the topic of competitive advantage using different conceptual approaches. In the 1990s, some strategic authors (Barney, 1991; Grant, 1996; Wernerfelt, 1984) proposed the Resource-Based View of firm (RBV) as an alternative strategy to Porter’s proposals. They argue that the greatest variation in profitability between firms was not between firms in different industries, but between firms in the same industry. This suggests that it is not so much differences in the structural factors within industry that determines profitability of firms, but what is inside an organization, resources or assets that allows them to compete. The combined work of Wernerfelt (1984), Rumelt (1984) and Barney (1986), has been mentioned as a reference of the contemporary benchmarks to the study of sustainable competitive advantage. In today's economy, where intangible assets have become the main reason of competitive advantage, the organizations required tools such as the Balanced Scorecard (BSC) to monitor and measure the strategy implementation, including the initiatives involving investments in IS/IT.